Developmental Enamel Defects Mimicking Mulberry Molars in a Syphilis-Negative Patient: A Case Report - Sangeetha Ramu; Rithi Murthy; Thrishika Muniyaiah; Darshana Sachin Nayak (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Mulberry molars are typically representing oral signs of congenital syphilis, characterized by multiple globular enamel cusps on the occlusal surfaces of first permanent molars. But sometimes, these morphological features can be seen in persons who never had syphilis or physiological evidence of it. Case Presentation: A case of a 12-year-old female patient presenting with characteristic mulberry molars involving all four first permanent molars. The patient’s medical and family history was non-contributory, and both Venereal Disease Research Laboratory (VDRL) and Treponema pallidum hemagglutination tests were negative, ruling out congenital syphilis. On clinical examination, multiple globular cuspal protuberance without caries or occlusal interference. Conservative management was followed, emphasizing periodic monitoring and topical fluoride application. This case highlights the possibility of non-syphilitic etiologies including local, systemic, genetic, or environmental condition which is a contributing factor for enamel developmental defects resembling mulberry molars. Conclusion: Mulberry molars can occur irrespective of congenital syphilis. It is important to know this rare occurrence for diagnostic purposes. Thus, this particular case requires teamwork between the dentist and the paediatrician to avoid diagnostic errors.